1982
DOI: 10.1530/jrf.0.0650215
|View full text |Cite
|
Sign up to set email alerts
|

The induction of ovulation and luteal function in seasonally anoestrous ewes treated with small-dose multiple injections of Gn-RH

Abstract: Seasonally anoestrous ewes were injected i.v. with 250, 500 or 1000 ng Gn-RH at 2-h intervals for 8 days (2 sheep/treatment). Each injection of 250 or 500 ng Gn-RH resulted in a transient rise in plasma LH concentrations. Treatment with 1000 ng Gn-RH per injection resulted in a more sustained rise in plasma LH concentrations in 1 of 2 sheep during the early part of the treatment period. A preovulatory-type LH peak occurred 17-48 h after the start of treatment in all ewes, with a second preovulatory-type peak 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
1
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 12 publications
8
47
1
1
Order By: Relevance
“…In anovular ewes, progesterone treatment prior to either the introduction of rams or treatment with GnRH, results in normal functioning of the corpora lutea that develop following the first ovulation (Hunter et al 1971;Oldham et al 1980;McLeod et at. 1982;Martin and Scaramuzzi 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In anovular ewes, progesterone treatment prior to either the introduction of rams or treatment with GnRH, results in normal functioning of the corpora lutea that develop following the first ovulation (Hunter et al 1971;Oldham et al 1980;McLeod et at. 1982;Martin and Scaramuzzi 1983).…”
Section: Discussionmentioning
confidence: 99%
“…1982;Martin and Scaramuzzi 1983). It has been suggested that this effect may be due to progesterone delaying the onset of the induced LH surge, thereby allowing adequate follicular development to take place before the induction of ovulation (Hare sign and Lamming 1978;McLeod et at. 1982;Pearce et at.…”
Section: Discussionmentioning
confidence: 99%
“…The premature demise of the corpora lutea after exogenous gonadotropin stimulation is a poorly understood cause of embryo recovery failure that is reported following gonadotropin-releasing hormone (GnRH)-induced ovulation in anestrous ewes (McLeod et al, 1982), although progestagen priming before ovulation induction eliminates premature luteolysis in those females (McLeod et al, 1984;Southee et al, 1988). Inadequate luteal function has also been reported in superovulated ewes following oestrous synchronization using a dual prostaglandin injection treatment (Trounson et al, 1976;Schiewe et al, 1991).…”
Section: Luteal Activitymentioning
confidence: 99%
“…The CL formed tend to be smaller and secrete less progesterone in vivo and in vitro than CL of the breeding season (McNeilly & Land 1979. Increasing the frequency of LH (McNeilly et al 1982) or GnRH pulses (Crighton et al 1975, McLeod et al 1982a, 1982b, Southee et al 1988a, 1988b to mimic the final stages of follicular maturation during the breeding season increased ovulation rate during seasonal anoestrus but still gave rise frequently to abnormal CL. However, the incidence of adequate luteal phases during anoestrus was increased significantly by progesterone pretreatment prior to induction of ovulation with GnRH (McLeod et al 1982b, Legan et al 1985.…”
Section: Introductionmentioning
confidence: 99%
“…A number of different mechanisms have been suggested to be responsible for the formation of inadequate luteal phases in sheep, including defective maturation of the preovulatory follicle (Keisler & Keisler 1989, Hunter et al 1986, White et al 1987, Southee et al 1988a, Khalid et al 1997, Lund et al 1999, Bartlewski et al 2001, perhaps due to an inappropriate pattern of LH stimulation of the follicle prior to the LH surge (McLeod et al 1982a, Wright et al 1983, attenuation of the LH surge (Bartlewski et al 2004), inadequate luteinization (Atkinson 1988, Hunter et al 1988, inappropriate luteal support of the new CL (Hunter et al 1988) and/or increased susceptibility to luteolytic stimuli (Hunter et al 1989, Beard & Hunter 1996 arising from the uterus (Southee et al 1988b, Hu et al 1991, though see Rahmanian and Murdoch 1987).…”
Section: Introductionmentioning
confidence: 99%